2014
DOI: 10.1177/1046878114530814
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration Through Simulation

Abstract: Background It has been suggested in the literature that virtual worlds can be an environment in which informal learning by participants can succeed through communication and collaboration, and that it would be valuable to investigate the extent to which the processes and principles underpinning this informal learning can be transferred to a formal learning context. The literature shows, however, a wide evidence gap. Aim This article reports on the initial findings from empirical research currently in progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…These findings support the applicability of using the game in a real school setting. Scullion, Livingstone, and Stansfield (2014) indicated that an immersive 3D virtual environment could be used to expand formal education. It also enables learners to be engaged and motivated.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the applicability of using the game in a real school setting. Scullion, Livingstone, and Stansfield (2014) indicated that an immersive 3D virtual environment could be used to expand formal education. It also enables learners to be engaged and motivated.…”
Section: Discussionmentioning
confidence: 99%
“…While we have placed a high value on the debriefing process (and we will continue to do so), we know that the experience is the most important part of simulation and gaming. It is during the experience that engagement and collaboration occur, and new knowledge is considered through the actions of trial and error (Scullion, Livingstone, & Stansfield, 2014, p. 398; Whitton, 2011, p. 597). In the learning environment and during the experience, the learning community reinforces both skill and knowledge (Harviainen, 2012, p. 518).…”
mentioning
confidence: 99%